(untitled) (The International Journal for Scientific Research, 2023)
Introduction: The quality of primary healthcare is crucial for ensuring efficient and effective patient care, particularly in rapidly evolving healthcare systems like that of Saudi Arabia. With ongoing reforms aimed at improving healthcare delivery, there is a pressing need to assess the state of quality control within primary healthcare settings. This systematic review aimed to evaluate the effectiveness of various quality control interventions implemented in primary healthcare centers in Saudi Arabia, focusing on their impact on patient care and system efficiency. Methods: The review strictly included interventional studies and clinical trials published in the last years up to 2022, employing a comprehensive search across multiple databases including PubMed, Scopus, Web of Science, and the Cochrane Library. Inclusion criteria were set to consider only studies that directly addressed quality control measures within primary healthcare settings in Saudi Arabia, with clear intervention and outcome measures. The analysis synthesized data on the types of interventions, sample sizes, and effectiveness, including risk ratios and percentage improvements with their confidence intervals. Results: Seven studies were included, revealing a range of interventions from EHR implementations to provider training programs and patient feedback systems. Key findings include a 55% reduction in medication errors following EHR system implementation, a 35% increase in compliance with national quality standards post-provider training, a 20% increase in patient satisfaction with the introduction of patient feedback systems, and a 30% improvement in patient outcomes from clinical guideline updates for chronic disease management. Conclusions: The review demonstrates that targeted interventions can significantly enhance quality control in primary healthcare settings in Saudi Arabia, with notable improvements in medication accuracy, compliance with quality standards, patient satisfaction, and clinical outcomes. These findings highlight the potential of comprehensive, integrated quality control measures to advance patient care and healthcare system efficiency.